Prevalence and Antibiogram of Bacterial Uropathogens of Urinary Tract Infections from a Tertiary Care Hospital of Bangladesh - Sanjee, S. A.; Karim, M. E.; Akter, T.; Parvez, M. A. K.; Hossain, M.; Jannat, B.; Pervin, S. (Journal of Scientific Research, 2017)
Urinary tract infections (UTIs) are one of the most frequently occurring infections majority of which are caused by multi-drug resistant (MDR) uropathogens. Hence, the present study was designed to find out the prevalence of bacterial pathogens causing UTIs and to determine their antibiotic resistance patterns against different classes of antibiotics. Clean-catch midstream urine samples were collected from 200 UTI patients of different sex and age groups. The uropathogens were isolated using Hi-Chrome UTI agar, Blood agar, MacConkey agar and then subjected to antibiotic susceptibility analysis against nine antibiotics of different classes using Kirby-Bauers disc diffusion method. From 55.08% positive samples, it was found that females were more prone to UTIs than males and in both cases; the prevalence rate was higher in the age group 21-40 years (33%). Among the uropathogens, E.coli was the predominant etiological agent (57.38%) followed by Enterococcus sp. (36.06%), Pseudomonas aeruginosa (3.28%) and Staphylococcus aureus (3.28%). The pathogens showed remarkable amount of sensitivity against Gentamicin and Ciprofloxacin. The present experiment can be helpful for the clinicians in finding proper drugs in the developing countries like Bangladesh where multi-drug resistance problem has just complicated the treatment of UTIs.